PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 14 PAUH KOTA PADANG - Kurniasari, Ningrum Adji; Anita, Yesi; Muhammadi, Muhammadi; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to describe the improvement in Pancasila Education learning outcomes using the Problem Based Learning (PBL) model in class V of SDN 14 Pauh, Padang City. This research applies a type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 19 students consisting of 8 men and 11 women. The results of this research show an increase in: a) teaching modules in cycle I with an average of 85.41% (Good) and cycle II 95,83% (very good), b) implementation in the teacher aspect of cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good), while implementation in the student aspect of cycle I averaged 82.14% (Good) and cycle II 96.42% (Very Good), c) assessment of students in improving results learning in cycle I obtained 74.94% and cycle II with an average of 85.76%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve Pancasila Education learning outcomes in class V.